THE INFLUENCE OF THE IHSG, BI RATE, AND ECONOMIC GROWTH ON THE OUTSTANDING VALUE OF CORPORATE SUKUK IN INDONESIA - Nopijal Rizki Rahman; Hafas Furqani; Khirul Amri (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the effects of the Composite Stock Price Index (IHSG), the BI Rate, and economic growth on the outstanding value of corporate sukuk in Indonesia. The study employs a quantitative approach using multiple linear regression analysis (Ordinary Least Squares) applied to secondary data obtained from official publications of relevant authorities during the research period. All variables are transformed into logarithmic form to allow the regression coefficients to be interpreted as elasticities. The results show that, partially, the Composite Stock Price Index (IHSG) has a positive and significant effect on the outstanding value of corporate sukuk, with a coefficient of 3.940 and a probability value of 0.000, indicating that a 1 percent increase in IHSG increases the outstanding value of corporate sukuk by 3.94 percent. The BI Rate does not have a significant effect, with a probability value of 0.405. Meanwhile, economic growth has a negative and significant effect, with a coefficient of −0.096 and a probability value of 0.000. Simultaneously, the three variables significantly affect the outstanding value of corporate sukuk, with an R-squared value of 0.735.